First report of African tick-bite fever in a South American traveler. (11th May 2018) - Angerami, Rodrigo N; Krawczak, Felipe S; Nieri-Bastos, Fernanda A; Santos, Fabiana; Medorima, Claudio; Resende, Mariângela Ribeiro; Labruna, Marcelo B
We report a clinical case of African tick-bite fever in a Brazilian traveler right after his return from South Africa. Definitive diagnosis was supported by seroconversion between acute-phase and convalescent-phase serum samples, detection of rickettsial DNA in skin lesions, and in vitro culture of Rickettsia africae from the patient's skin. Most of the previous reported cases of African tick-bite fever were confirmed solely by serological or/and molecular methods. Through this first confirmed case of African tick-bite fever in Brazil, it is quite possible that other cases are occurring unnoticed by the health authorities, requiring a greater vigilance in traveler's medicine in South America.